Adherence to a Western dietary pattern and risk of bladder cancer: A pooled analysis of 13 cohort studies of the Bladder Cancer Epidemiology and Nutritional Determinants international study. Issue 12 (20th July 2020) - Dianatinasab, Mostafa; Wesselius, Anke; Salehi‐Abargouei, Amin; Yu, Evan Y. W.; Brinkman, Maree; Fararouei, Mohammad; van den Brandt, Piet; White, Emily; Weiderpass, Elisabete; Le Calvez‐Kelm, Florence; Gunter, Marc; Huybrechts, Inge; et al.
Abstract: Little is known about the association of diet with risk of bladder cancer. This might be due to the fact that the majority of studies have focused on single food items, rather than dietary patterns, which may better capture any influence of diet on bladder cancer risk. We aimed to investigate the association between a measure of Western dietary pattern and bladder cancer risk. Associations between adherence to a Western dietary pattern and risk of developing bladder cancer were assessed by pooling data from 13 prospective cohort studies in the "BLadder cancer Epidemiology and Nutritional Determinants" (BLEND) study and applying Cox regression analysis. Dietary data from 580 768 study participants, including 3401 incident cases, and 577 367 noncases were analyzed. A direct and significant association was observed between higher adherence to a Western dietary pattern and risk of bladder cancer (hazard ratio (HR) comparing highest with lowest tertile scores: 1.54, 95% confidence interval (CI): 1.37, 1.72; P ‐trend = .001). This association was observed for men (HR comparing highest with lowest tertile scores: 1.72; 95% CI: 1.51, 1.96; P ‐trend = .001), but not women ( P ‐het = .001). Results were consistent with HR above 1.00 after stratification on cancer subtypes (nonmuscle‐invasive and muscle‐invasive bladder cancer). We found evidence that adherence to a Western dietary pattern is associated with an increased risk of bladder cancer for men but not women. Abstract : What's new? Does diet affect bladder‐cancer risk? Individual foods are rarely eaten in isolation, but little is known about the impact of overall dietary habits. In this large, prospective study, the authors found that greater adherence to a Western dietary pattern was associated with a significantly increased risk of bladder cancer in men. (Surprisingly, the same effect was not seen in women.) Further research is needed to identify the specific food types responsible and their mechanisms of bladder carcinogenesis. However, education to encourage changes in general dietary habits may provide a valuable public‐health benefit.